Lithium secondary battery and composite member
By forming a spacer on the separator of the lithium secondary battery and combining a composite material layer, the problems of large electrode group expansion and poor circulation characteristics during charging of the lithium secondary battery are solved, and the effects of small electrode group expansion and good circulation characteristics are achieved.
Patent Information
- Application Number
- CN202380062345.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-07-25
- Publication Date
- 2025-04-11
AI Technical Summary
The electrode group of existing lithium secondary batteries expands greatly during charging, and the circulation characteristics are poor, making it difficult to further increase the capacity.
By forming a spacer on the separator of the lithium secondary battery and combining a composite material layer, the shortest distance and width of the spacer are controlled within a specific range to suppress expansion of the electrode group and the decrease in the fluidity of the electrolyte.
A lithium secondary battery with small electrode group expansion and good circulation characteristics during charging is realized, which significantly improves the battery capacity maintenance rate.
Smart Images

Figure CN119816971A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium secondary battery and a composite member. Background Art
[0002] Non-aqueous electrolyte secondary batteries are used for ICT, vehicle-mounted, and power storage purposes such as personal computers and smart phones. In such applications, non-aqueous electrolyte secondary batteries are required to have a further high capacity. As a high-capacity non-aqueous electrolyte secondary battery, a lithium ion battery is known. The high capacity of a lithium ion battery can be achieved by, for example, using alloy active materials such as graphite and silicon compounds as negative electrode active materials. However, the high capacity of lithium ion batteries is reaching its limit.
[0003] As a non-aqueous electrolyte secondary battery with a higher capacity than lithium-ion batteries, lithium secondary batteries (lithium metal secondary batteries) are promising. In lithium secondary batteries, lithium metal is deposited at the negative electrode during charging, and the lithium metal is dissolved in the non-aqueous electrolyte during discharge. Various proposals have been proposed for lithium secondary batteries in the past.
[0004] Patent document 1 (International Publication No. 2020 / 066254) discloses "a lithium secondary battery comprising: a positive electrode comprising a positive electrode collector and a positive electrode mixture layer containing a positive electrode active material; a negative electrode comprising a negative electrode collector opposite to the positive electrode; a separator arranged between the positive electrode and the negative electrode; and a non-aqueous electrolyte having lithium ion conductivity, the positive electrode active material comprising a composite oxide, the composite oxide comprising lithium and a metal M other than lithium, the metal M comprising at least a transition metal, lithium metal is precipitated at the negative electrode during charging, and the lithium metal is dissolved from the negative electrode during discharging, the first length of the positive electrode collector in a first direction D1 is smaller than the second length in a second direction D2 intersecting the first direction, a separator is provided between the positive electrode and the separator in such a manner as to form a space for accommodating the lithium metal between the positive electrode and the negative electrode, and a straight line SL can be drawn along the first direction D1 in such a manner as to pass through more than three of the separators.".
[0005] Prior Art Literature
[0006] Patent Document 1: International Publication No. 2020 / 066254 Summary of the invention
[0007] Nowadays, there is a demand for further improvement in the characteristics of lithium secondary batteries. One of the objects of the present disclosure is to provide a lithium secondary battery having small expansion of an electrode group (for example, expansion near a negative electrode) during charging and excellent cycle characteristics.
[0008] One aspect of the present disclosure relates to a lithium secondary battery. The lithium secondary battery comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, a spacer disposed on the separator, and a non-aqueous electrolyte having lithium ion conductivity, wherein the negative electrode is an electrode in which lithium metal is precipitated during charging and dissolved during discharge, the separator comprises a substrate layer and a composite material layer, and when viewed from above, the shortest distance from any point on the separator to the outer edge of the separator is less than 1.5 mm, and the width of the separator is greater than 0.01 mm, and the composite material layer contains a polymer and an inorganic particle.
[0009] Another aspect of the present disclosure relates to a composite component, which includes a diaphragm and a spacer, wherein the diaphragm has a substrate layer and a composite material layer, the shortest distance from any point on the spacer to the outer edge of the spacer is less than 1.5 mm when viewed from above, and the width of the spacer is greater than 0.01 mm, and the composite material layer contains a polymer and inorganic particles.
[0010] According to the present disclosure, it is possible to obtain a lithium secondary battery in which expansion of the electrode group (for example, expansion near the negative electrode) during charging is small and cycle characteristics are excellent.
[0011] The novel features of the present invention are described in the claims, and the present invention relates to both aspects of structure and content, and together with other objects and features of the present invention, will be better understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a longitudinal sectional view schematically showing an example of a lithium secondary battery according to an embodiment of the present disclosure.
[0013] Figure 2 It is schematically indicated Figure 1 A cross-sectional view of a portion of a lithium secondary battery is shown.
[0014] Figure 3 It is a top view showing an example of a pattern of a spacer.
[0015] Figure 4 yes Figure 3 A partial enlarged view of .
[0016] Figure 5 It is a top view showing another example of the pattern of the spacer.
[0017] Figure 6 It is a top view showing another example of the pattern of the spacer.
[0018] Figure 7 It is a top view showing another example of the pattern of the spacer. DETAILED DESCRIPTION
[0019] The following examples illustrate the embodiments of the present disclosure, but the embodiments of the present disclosure are not limited to the examples described below. In the following description, specific numerical values and materials are sometimes exemplified, but other numerical values and other materials can also be applied as long as the invention of the present disclosure can be implemented. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, and can also be referred to as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit are exemplified for numerical values of specific physical properties and conditions, as long as the lower limit is not above the upper limit, any one of the exemplified lower limits and any one of the exemplified upper limits can be arbitrarily combined.
[0020] (Lithium secondary battery)
[0021] A lithium secondary battery (hereinafter sometimes referred to as "lithium secondary battery (L)") of one embodiment of the present disclosure includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, a separator formed on the separator, and a non-aqueous electrolyte having lithium ion conductivity. The negative electrode is an electrode at which lithium metal is precipitated during charging and dissolved during discharging. The separator includes a substrate layer and a composite material layer. When viewed from above, the shortest distance from any point on the separator to the outer edge of the separator is less than 1.5 mm, and the width of the separator is greater than 0.01 mm. The composite material layer contains a polymer and inorganic particles.
[0022] The term "planar viewing" means viewing an object placed on a flat surface from the normal direction of the surface. For example, viewing a spacer formed on a diaphragm from above means placing the diaphragm on a flat surface and viewing the spacer from the normal direction of the surface.
[0023] The spacer may include linear convex portions, and may include dot-shaped (island-shaped) convex portions. The spacer may consist of only linear convex portions, may consist of only dot-shaped convex portions, or may consist of both linear convex portions and dot-shaped convex portions. The planar shape of the dot-shaped convex portions is not particularly limited, and may be circular (perfectly circular or elliptical), polygonal (triangular, quadrilateral, etc.), etc.
[0024] In the following, the shortest distance from any point on the spacer to the outer edge of the spacer when viewed from above is sometimes referred to as the "shortest distance D". In the following, the width of the spacer when viewed from above is sometimes referred to as the "width W". In the case where the spacer includes a linear protrusion, the width W of the linear protrusion is the length (width) of the linear protrusion in a direction perpendicular to the direction in which the linear protrusion extends when viewed from above. In the case where the spacer includes a point-shaped protrusion, the width W of the point-shaped protrusion is the shortest diameter of the plane shape passing through the center of gravity of the plane shape of the point-shaped protrusion when viewed from above.
[0025] A space (hereinafter sometimes referred to as "space (S)") is formed between the positive electrode and the negative electrode by the spacer. By making the width W greater than 0.01 mm, it is easy to maintain the space S. As a result, the expansion of the electrode group during charging can be suppressed. In addition, by making the shortest distance D less than 1.5 mm, the reduction in the fluidity of the electrolyte can be suppressed. As a result, the cycle characteristics of the lithium secondary battery (L) can be improved.
[0026] As a result of the research, the inventors of the present application have newly found that the effect is greatly improved by not only setting the shortest distance D and the width W to the above ranges but also combining with a predetermined composite material layer. The present disclosure is based on this new finding.
[0027] The reason why a significant effect can be obtained by combining a spacer having the shortest distance D and the width W within the above range with a composite material layer is not yet clear. There is the following possibility: the composite material layer, due to the high liquid expansion of the electrolyte and high strength, obtains a significant effect by combining with the above spacer.
[0028] In a lithium secondary battery (L), the space between the positive electrode and the negative electrode is ensured by a separator. During charging, lithium metal is deposited on the surface of the negative electrode. By having a space between the positive electrode and the negative electrode, the expansion of the electrode group during the deposition of lithium metal can be suppressed.
[0029] In addition, the separator of the lithium secondary battery (L) includes a composite material layer formed on the surface of the substrate layer. Through the composite material layer, it is possible to suppress the shrinkage of the substrate layer when the temperature of the electrode group rises excessively. If the substrate layer shrinks, the positive and negative electrodes are easily short-circuited, so the temperature of the electrode group is prone to further rise. By including a composite material layer in the separator, it is possible to suppress the shrinkage of the substrate layer, so it is possible to suppress the temperature of the electrode group from further rising.
[0030] In addition, when a separator is formed on the positive electrode, the separator covers the positive electrode surface, so the transfer of lithium ions based on the positive electrode active material is partially hindered. As a result, the cell capacity is sometimes reduced. In contrast, in a lithium secondary battery (L), a separator is formed on the diaphragm, so the above-mentioned problem can be avoided.
[0031] Lithium secondary batteries (L) are also called lithium metal secondary batteries. In the negative electrode of such batteries, lithium metal is deposited during charging and dissolved during discharging. Specifically, the negative electrode has at least a negative electrode current collector, and lithium metal is deposited on the negative electrode current collector.
[0032] In a lithium secondary battery (L), more than 70% of the rated capacity, for example, is realized by the precipitation and dissolution of lithium metal. The movement of electrons in the negative electrode during charging and discharging is mainly caused by the precipitation and dissolution of lithium metal in the negative electrode. Specifically, 70 to 100% (for example, 80 to 100%, 90 to 100%) of the movement of electrons in the negative electrode during charging and discharging (current in another viewpoint) is caused by the precipitation and dissolution of lithium metal. That is, the negative electrode of the lithium secondary battery (L) is different from the negative electrode in which the movement of electrons in the negative electrode during charging and discharging is mainly caused by the absorption and release of lithium ions based on the negative electrode active material (graphite, etc.). The negative electrode of one example does not contain a negative electrode active material (graphite, etc.) that absorbs and releases lithium ions.
[0033] Hereinafter, the positive electrode, the negative electrode and the separator are sometimes collectively referred to as an "electrode group". The positive electrode, the negative electrode and the separator may be wound in a manner such that the separator is disposed between the positive electrode and the negative electrode. In the case of forming a wound electrode group, a strip-shaped positive electrode, a strip-shaped negative electrode and a strip-shaped separator may be used. Alternatively, the positive electrode, the negative electrode and the separator may also be stacked. For example, a flat positive electrode, a flat negative electrode and a flat separator may also be stacked. That is, the electrode group may be a wound electrode group or a stacked electrode group.
[0034] (Diaphragm)
[0035] As described above, the separator includes a substrate layer and a composite material layer. The separator has a first main surface facing the negative electrode and a second main surface facing the positive electrode. The separator may be formed on the first main surface or on the second main surface.
[0036] (Base material layer)
[0037] As the substrate layer, a porous sheet having ion permeability and insulation can be used. Examples of porous sheets include porous films, woven fabrics, nonwoven fabrics, etc. The material of the separator is not particularly limited and can be a polymer material. Examples of polymer materials include polyolefin resins, polyamide resins, cellulose, etc. Examples of polyolefin resins include polyethylene, polypropylene, and copolymers of ethylene and propylene, etc. The substrate layer may also contain additives as needed. As additives, inorganic fillers, etc. can be cited. As the substrate layer, a sheet used as a separator for a lithium secondary battery can also be used.
[0038] (Spacer)
[0039] The width W of the spacer when viewed from above is 0.01 mm or more, and may be 0.02 mm or more, 0.2 mm or more, or 0.5 mm or more. The width W may be 2.0 mm or less, 1.5 mm or less, 1.0 mm or less, or 0.6 mm or less. The width W may be in the range of 0.01 to 2.0 mm, 0.02 to 2.0 mm, 0.2 to 2.0 mm, or 0.5 to 2.0 mm. In these ranges, the upper limit may be 1.5 mm, 1.0 mm, or 0.6 mm.
[0040] In a linear convex portion that does not intersect with other convex portions, the shortest distance D is half of the width W. When a linear convex portion of width W and a linear convex portion of width W are orthogonal to each other, the shortest distance D at the center of the intersection is For example, when a linear convex portion with a width W of 2 mm and a linear convex portion with a width W of 2 mm are perpendicular to each other, the shortest distance D at the center of the intersection is about 1.4 mm (more specifically, ).
[0041] The shortest distance D is less than 1.5 mm, and may be less than 1.4 mm (including less than 1.45 mm), less than 1.0 mm, less than 0.8 mm, less than 0.5 mm, or less than 0.3 mm. As long as there is no contradiction in the description, any of the upper limits of the shortest distance D exemplified herein and any of the lower limits of the width W mentioned above may be arbitrarily combined. For example, the width W may be any one of greater than 0.01 mm, greater than 0.02 mm, greater than 0.2 mm, and greater than 0.5 mm, and the shortest distance D may be less than 1.5 mm, less than 1.4 mm, less than 1.0 mm, less than 0.8 mm, or less than 0.5 mm. Here, the upper limit of the shortest distance D may also be greater than 0.1 mm. Select from the value.
[0042] The spacer may contain a resin (e.g., an insulating resin) or a resin and particles. The spacer may be composed of only a resin or a resin and particles. The proportion of the resin in the spacer may be 10% by volume or more, 30% by volume or more, or 50% by volume or more, or 100% by volume or less or 80% by volume or less. The content of particles in the spacer may be lower than the content of particles in the composite material layer.
[0043] Examples of the resin material include fluorine-containing resins such as polyvinylidene fluoride (PVdF) and polytetrafluoroethylene, fluorine-containing rubbers such as vinylidene fluoride-tetrafluoroethylene copolymers and ethylene-tetrafluoroethylene copolymers, styrene-butadiene copolymers or their hydrides, acrylonitrile-butadiene copolymers or their hydrides, methacrylate-acrylate copolymers, styrene-acrylate copolymers, acrylonitrile-acrylate copolymers, ethylene propylene rubber, polyvinyl alcohol, rubbers such as polyvinyl acetate, cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose, acrylic resins such as acrylic acid-methacrylic acid copolymers, polyphenylene ether, polysulfone, polyether sulfone, polyphenylene sulfide, polyetherimide, polyimide, polyamides such as wholly aromatic polyamides (aromatic polyamides), polyamideimide, polyacrylonitrile, polyvinyl alcohol, polyether, polyacrylic acid, polymethacrylic acid, polyester, polyolefin, polysiloxane resin, polyurethane resin, melamine resin, urea resin, and epoxy resin.
[0044] Among the above-mentioned resin materials, polyimide, polyvinylidene fluoride, acrylonitrile-acrylate copolymer, etc. are preferred as materials that are impermeable to lithium ions, and polyimide may also be used. The non-porous spacer formed by these resin materials above a certain height is a layer that is impermeable to lithium ions. The average height of the spacer may be more than 3 times, more than 5 times, or more than 10 times the average thickness of the composite material layer, and may be less than 100 times, less than 30 times, or less than 20 times the average thickness of the composite material layer.
[0045] The particles may be inorganic particles or organic particles. Among them, inorganic particles such as insulating metal oxides, metal hydroxides, metal nitrides, metal carbides, and metal sulfides may be listed. As metal oxides, aluminum oxide (aluminum oxide, boehmite), magnesium oxide, titanium oxide (titanium dioxide), zirconium oxide, silicon oxide (silicon dioxide), etc. may be listed as preferred materials. As metal hydroxides, aluminum hydroxide may be listed. As metal nitrides, silicon nitride, aluminum nitride, boron nitride, titanium nitride, etc. may be listed. As metal carbides, silicon carbide, boron carbide, etc. may be listed. As metal sulfides, barium sulfate may be listed. In addition, minerals such as aluminosilicates, layered silicates, barium titanate, and strontium titanate may also be used. Among them, aluminum oxide, silicon dioxide, titanium dioxide, etc. are preferably used.
[0046] The average particle size of the particles is not particularly limited, and may be greater than 0.1 μm or greater than 0.5 μm, and may be less than 10 μm, less than 5 μm, or less than 2 μm. The average particle size can be measured by the following method. First, a cross section of the spacer in the thickness direction of the diaphragm is photographed with an electron microscope to obtain an image of the cross section. Next, the image is subjected to image processing such as binarization to determine the portion of the particle. Next, the diameter of a circle having the same area as the area of the cross section of each particle (equivalent circle diameter) can be calculated, and the arithmetic mean of the calculated equivalent circle diameter is taken as the average particle size. The arithmetic mean can be calculated from, for example, more than 100 particles. Furthermore, the average particle size of other particles contained in the electrode plate and the diaphragm can also be calculated in the same way.
[0047] When the spacer contains a resin material and particles, the content of the particles in the spacer is preferably 50% by volume or less. This makes it easy to ensure sufficient strength of the spacer.
[0048] Generally, even if the shortest distance D is small, the lower the average height Hs of the spacer is, the more the strength of the spacer can be ensured. The ratio D / Hs of the shortest distance D and the average height Hs can be 0.05 or more, 0.10 or more, 0.15 or more, 1.0 or more, or 5.0 or less, 10 or less, 20 or less, or 50 or less. By setting the ratio D / Hs to a range of 0.10 to 20, it is possible to obtain an effect such as easy maintenance of the space between the electrodes.
[0049] The average height Hs of the spacer may be greater than the sum Tw of the average thickness Tb of the substrate layer and the average thickness Tt of the composite material layer. The ratio Hs / Tw of the average height Hs and the sum Tw may be greater than 1, greater than 1.5, greater than 2, or greater than 3. The ratio Hs / Tw may be less than 10, less than 8, less than 5, or less than 4. By setting the ratio to be greater than 1.5, the expansion of the electrode group can be particularly suppressed.
[0050] The average height Hs can be measured by the following method. First, a cross section of the diaphragm in the thickness direction of the diaphragm is photographed with an electron microscope to obtain an image of the cross section. Then, in the image, any 20 locations among the spacers are selected to measure the height of the spacers at the locations. Then, the heights of the 20 locations measured are arithmetic averaged, and the average value obtained is taken as the average height Hs. The average thickness Tb and the average thickness Tt can also be measured using the same steps.
[0051] The average thickness Tb of the substrate layer can be 5 μm or more or 10 μm or more, and can be 30 μm or less or 20 μm or less. The average thickness Tt of the composite material layer can be 1 μm or more or 2 μm or more, and can be 5 μm or less or 3 μm or less. The average height Hs of the spacer can be 10 μm or more or 20 μm or more, and can be 100 μm or less, 50 μm or less, 40 μm or less or 30 μm or less. These heights and thicknesses also vary according to the composition of the positive and negative electrodes, and can take values outside the range illustrated here. Furthermore, in order to make the interval between the plates formed by the spacer as constant as possible, the spacer is usually formed in a manner that the height is as constant as possible.
[0052] The spacer may include a non-porous structure that is impermeable to lithium ions. Such a spacer can be achieved by forming it under conditions where it does not become porous when forming the spacer. The method for forming a spacer with a non-porous structure is not particularly limited, and a known method can be used. For example, a spacer with a non-porous structure can be formed by printing the constituent materials of the above-mentioned spacer on a diaphragm in the form of ink. Furthermore, in this specification, the so-called "lithium ion impermeability" means that the amount that affects the characteristics and shape of the battery cannot be penetrated, including the situation where an amount of lithium ions that can be regarded as substantially impermeable moves in the spacer.
[0053] In the case where the separator allows lithium ions to pass through, the lithium ions pass through the separator during charging. The lithium ions that have passed through the separator are precipitated between the substrate layer and the negative electrode in the portion where the separator is formed. As a result, the thickness of the electrode group in the stacking direction becomes thicker. Therefore, the separator preferably does not allow lithium ions to pass through. Furthermore, in the case of a wound electrode group, the so-called stacking direction refers to the radial direction of the wound electrode group.
[0054] The area S1 of the separator can be less than 30% of the area S0 of the diaphragm. If it is set to this range, the space for the precipitation of lithium metal can be fully ensured. Furthermore, area S1 and area S0 are respectively the areas of the diaphragm when observing the diaphragm from the separator side. The ratio S1 / S0 of area S1 and area S0 can be less than 0.20 (less than 20%) or less than 0.10, and can be greater than 0.03 (more than 3%) or greater than 0.05. By setting the ratio to more than 0.05 (more than 5%), the effect of suppressing excessive temperature rise of the electrode group can be improved. Furthermore, areas S0 and S1 are areas when viewed from above. In other words, areas S0 and S1 are the areas of the diaphragm and separator when observed from above, respectively.
[0055] The cross-sectional shape of the linear protrusion in the direction perpendicular to the direction in which the linear protrusion extends is not limited, and may be rectangular or conical. For example, the cross-sectional shape may be a trapezoid whose width narrows as it moves away from the diaphragm. Similarly, the cross-sectional shape of the dot-shaped protrusion is not limited, and may be rectangular or conical (e.g., trapezoidal).
[0056] In one viewpoint, the linear protrusions are ridge-shaped protrusions. From the viewpoint of enhancing the effect of suppressing an excessive temperature rise of the electrode group, the separator preferably includes the linear protrusions, but may be composed of only the linear protrusions.
[0057] The linear projections may be mesh-shaped projections. By making the mesh-shaped projections, the effect of suppressing the shrinkage of the substrate layer is improved, and thus the effect of suppressing the excessive temperature rise of the electrode group can be improved.
[0058] The planar shape of the linear protrusion may be a shape formed by combining polygons. An example of a mesh shape includes a shape formed by combining polygons in a manner of sharing edges. Polygons include triangles, quadrilaterals, hexagons, etc. Different types of polygons may also be combined. The planar shape of the linear protrusion may be a honeycomb shape. If it is a honeycomb-shaped protrusion, as described with respect to the mesh protrusion, the effect of suppressing excessive temperature rise of the electrode group can be improved. Alternatively, the linear protrusion may also include a plurality of linear protrusions arranged in a stripe shape.
[0059] The first resin constituting the spacer preferably has a higher heat resistance than the second resin constituting the substrate layer. Here, the so-called high heat resistance means that the decomposition temperature or melting point of the first resin is higher than the decomposition temperature or melting point of the second resin. Furthermore, the first resin and the second resin may each include a plurality of resins.
[0060] (Composite material layer)
[0061] The composite material layer is preferably a porous layer. The method for forming the porous composite material layer is not particularly limited, and a known method can be used. For example, the porous composite material layer can be formed by printing the material containing the above-mentioned inorganic particles on the substrate layer in the form of ink.
[0062] The separator includes at least one composite material layer. The composite material layer may be formed on the main surface on the positive electrode side of the two main surfaces of the substrate layer, may be formed on the main surface on the negative electrode side, or may be formed on each of the two main surfaces.
[0063] The composite material layer includes a polymer (hereinafter sometimes referred to as "polymer (PL)") and inorganic particles. The inorganic particles may include first particles and / or second particles. The first particles are particles of lithium-containing phosphate. The second particles are particles other than the first particles. The composite material layer is a layer that allows lithium ions to pass through.
[0064] The configuration of the positive electrode, negative electrode, substrate layer, composite material layer, separator and separator is not particularly limited except that the separator and separator are configured between the positive electrode and the negative electrode. The separator can be configured in a manner that the composite material layer is opposite to the positive electrode, or in a manner that the composite material layer is opposite to the negative electrode. By configuring the composite material layer on the positive electrode side, the substrate layer can be inhibited from deteriorating due to oxidation reaction. On the other hand, by configuring the composite material layer on the negative electrode side, the substrate layer can be inhibited from deteriorating due to reduction reaction.
[0065] The separator is formed on the diaphragm. The separator can be formed on the composite material layer or on the substrate layer. By forming the separator on the composite material layer, the effect of suppressing the thermal shrinkage of the substrate layer becomes particularly high. By forming the separator on the composite material layer, it is easy to obtain the effects of ensuring the battery capacity, improving the liquid expansibility of the electrolyte, and improving productivity. Examples of preferred configurations include the configurations of positive electrode / composite material layer / substrate layer / separator / negative electrode and positive electrode / substrate layer / composite material layer / separator / negative electrode.
[0066] The phosphate constituting the first particle may be at least one selected from lithium phosphate (Li3PO4), dilithium hydrogen phosphate (Li2HPO4) and lithium dihydrogen phosphate (LiH2PO4). Among them, lithium phosphate is preferred from the viewpoint of high effect of suppressing abnormal battery heating.
[0067] The average particle size of the first particle can be in the range of 0.1 μm to 1.0 μm (for example, a range of 0.1 μm to 0.5 μm, a range of 0.1 μm to 0.2 μm, a range of 0.1 μm to 0.19 μm). The average particle size of the first particle can be greater than 0.1 μm or greater than 0.15 μm. The average particle size of the first particle can be less than 1.0 μm, less than 0.5 μm, less than 0.3 μm, or less than 0.2 μm. By making the average particle size greater than 0.1 μm, sufficient pores required for the penetration of the electrolyte can be ensured. From the viewpoint of being able to form a high-density layer of the first particle, it is preferred that the average particle size be less than 1.0 μm.
[0068] As the polymer (PL), a polymer having a higher heat resistance than the main component of the substrate layer of the diaphragm can be used. The polymer (PL) preferably includes at least one selected from aromatic polyamides, aromatic polyimides and aromatic polyamide-imides. They are known as polymers with high heat resistance (polymers or resins in another viewpoint). From the viewpoint of heat resistance, aromatic polyamides, i.e., meta-type aromatic polyamides (meta-type fully aromatic polyamides) and para-type aromatic polyamides (para-type fully aromatic polyamides) are preferred. A preferred example of the polymer (PL) is meta-type aromatic polyamide. As the polymer (PL), known aromatic polyamides, aromatic polyimides and aromatic polyamide-imides can also be used.
[0069] Examples of aromatic polyamides (polymers (PL)) include polymers formed by polycondensing monomers having an aromatic skeleton and containing an amide bond in a repeating unit. Examples of aromatic polyamides (e.g., wholly aromatic polyamides) include meta-type aromatic polyamides (e.g., meta-type wholly aromatic polyamides) and para-type aromatic polyamides (e.g., para-type wholly aromatic polyamides). Wholly aromatic polyamides are also referred to as aromatic polyamides.
[0070] A preferred example of the second particle (inorganic particle) is a particle composed of an insulating inorganic compound that does not melt or decompose when the battery is abnormally heated. The second particle may be an inorganic particle generally used as an inorganic filler. Examples of the material of the second particle include oxides, oxide hydrates, hydroxides, nitrides, carbides, sulfides, etc., which may contain metal elements. The average particle size of the second particle may be greater than 0.2 μm and less than 2 μm.
[0071] Examples of oxides and oxide hydrates include aluminum oxide, boehmite, magnesium oxide, titanium oxide, zirconium oxide, silicon oxide, yttrium oxide, zinc oxide, etc. Examples of nitrides include silicon nitride, aluminum nitride, boron nitride, titanium nitride, etc. Examples of carbides include silicon carbide, boron carbide, etc. Examples of sulfides include barium sulfate, etc. Examples of hydroxides include aluminum hydroxide, etc.
[0072] In addition, the material of the second particle can also be a porous aluminosilicate such as zeolite, a layered silicate such as talc, barium titanate (BaTiO3), strontium titanate (SrTiO3), etc. From the viewpoint of insulation and heat resistance, at least one selected from alumina, boehmite, talc, titanium oxide and magnesium oxide can be used as the material of the second particle.
[0073] The average particle size of the second particles may also be within the range exemplified for the average particle size of the first particles.
[0074] The inorganic particles may include the first particles and the second particles other than the phosphate. In this case, the composite material layer may include the first layer containing the first particles and the second layer containing the second particles. According to this configuration, the effect of suppressing excessive temperature rise of the electrode group can be particularly improved. Furthermore, the composite material layer may also be composed of only the first layer or only the second layer.
[0075] The first layer and the second layer can be stacked on the main surface of the positive electrode side among the two main surfaces of the substrate layer, can be stacked on the main surface of the negative electrode side, and can also be stacked on different main surfaces. For example, the diaphragm and the spacer can have a laminated structure such as substrate layer / the first layer / the second layer / spacer, substrate layer / the second layer / the first layer / spacer, the first layer / the second layer / substrate layer / spacer or the second layer / the first layer / substrate layer / spacer. Alternatively, the first layer and the second layer can also be configured on the different main surfaces of the substrate layer. For example, the diaphragm and the spacer can also have a laminated structure such as the first layer / substrate layer / the second layer / spacer or the second layer / substrate layer / the first layer / spacer.
[0076] The first layer may include the first particle as a main component. The content of the first particle in the first layer may be in the range of 50 mass % to 99 mass %, in the range of 85 mass % to 99 mass %, or in the range of 90 mass % to 98 mass %. The content may be 50 mass % or more, 70 mass % or more, 85 mass % or more, or 90 mass %. The content may be 99 mass % or less, 98 mass % or less, or 95 mass % or less. If within these ranges, the first particle has sufficient surface area, and it is easy to inactivate lithium at high temperatures.
[0077] The first layer may contain a solid component other than the first particles. For example, the first layer may contain a binder, an inorganic substance other than the first particles (eg, inorganic particles), a polymer (PL), and the like.
[0078] When the first layer contains a binder, the content of the binder in the first layer may be in the range of 1% to 15% by mass, or in the range of 2% to 10% by mass. The content of the binder in the first layer may be 1% by mass or more, or 2% by mass or more. The content of the binder in the first layer may be 15% by mass or less, or 10% by mass or less.
[0079] The adhesive contained in the first layer is not particularly limited, and includes polyolefins (polyethylene, polypropylene, copolymers of ethylene and α-olefin, etc.), fluorine-containing resins (polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl fluoride, etc.), fluorine-containing rubbers (vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, ethylene-tetrafluoroethylene copolymers, etc.), styrene-butadiene copolymers and their hydrides, acrylonitrile-butadiene copolymers and their hydrides, acrylonitrile-butadiene-styrene copolymers and their hydrides, and N-vinylacetamide.
[0080] (Layer 2)
[0081] As described above, the second layer includes the second particles other than the first particles (phosphate particles). The second layer may include the first particles or may not include the first particles.
[0082] The second layer preferably contains the polymer (PL). The content of the polymer (PL) in the second layer may be in the range of 50% to 100% by mass (eg, 80% to 100% by mass, 90% to 100% by mass). The second layer may also be composed only of the polymer (PL).
[0083] The second layer may include the second particles as a main component. The content of the second particles in the second layer may be in the range of 50% to 99% by mass (e.g., the range of 85% to 99% by mass). In addition, in this case, the second layer may also include an adhesive. As an example of an adhesive, the adhesive exemplified in the description of the first layer can be used. The content of the second particles in the second layer may be more than 50% by mass, more than 70% by mass, more than 85% by mass, or more than 90% by mass. The content may be less than 99% by mass, less than 98% by mass, or less than 95% by mass.
[0084] The thickness of the first layer and the second layer may be independently in the range of 0.2 μm to 10 μm (e.g., in the range of 1 μm to 8 μm, in the range of 2 μm to 4 μm, in the range of 4 μm to 10 μm). For example, the thickness of the first layer may be in the range of 0.2 μm to 10 μm, and the thickness of the second layer may be in the range of 0.2 μm to 10 μm. The thickness of the first layer may be 0.2 μm or more, 0.3 μm or more, 0.5 μm or more, preferably 1 μm or more, more preferably 2 μm or more, further preferably 3 μm or more, and further preferably 4 μm or more. The thickness of the first layer may be 10 μm or less, 8 μm or less, 7 μm or less, or 5 μm or less. The thickness of the second layer may be 0.2 μm or more, 0.3 μm or more, 0.5 μm or more, preferably 1 μm or more, more preferably 2 μm or more, further preferably 3 μm or more, and further preferably 4 μm or more. The thickness of the second layer may be 10 μm or less, 8 μm or less, 7 μm or less, or 5 μm or less. When the thickness of at least one of the first layer and the second layer is 0.2 μm or more, it is advantageous in suppressing the rise in battery temperature during abnormal conditions. When the thickness of at least one of the first layer and the second layer is 10 μm or less, it is advantageous from the perspective of the electrical characteristics of the battery.
[0085] When the composite material layer includes the first particle, the temperature rise of the battery in an abnormal state can be particularly suppressed. The mechanism is not yet clear. As a possibility, it is conceivable that when the battery temperature rises abnormally, the first particle reacts with the lithium metal of the negative electrode, and the reactivity of the surface of the lithium metal decreases.
[0086] In another aspect, the present disclosure provides another lithium secondary battery (Z). Regarding the other lithium secondary battery (Z), the following (1) and (2) are different from the above-mentioned lithium secondary battery (L). The contents other than the following (1) and (2) are the same as those of the lithium secondary battery (L), so repeated descriptions are omitted.
[0087] (1) The shortest distance D is not limited.
[0088] (2) The spacer includes a linear projection, and the width W of the linear projection in a plan view is 0.01 mm or more and 2.0 mm or less.
[0089] (Method for Forming Diaphragm and Spacer)
[0090] The method for producing the separator is not particularly limited, and the separator can be produced by the following method. First, a substrate layer is prepared. A commercially available substrate layer can also be used. Next, a composite material layer is formed on the substrate layer.
[0091] The method for forming the composite material layer is not particularly limited, and the composite material layer can be formed by the following method. First, a slurry (or coating liquid) is formed by mixing the components of the composite material layer with a liquid component (dispersion medium). Then, the slurry (or coating liquid) is applied to the substrate layer to form a coating film, and the coating film is dried. In this way, a composite material layer can be formed. There is no particular limitation on the liquid component used to form the slurry (or coating liquid). Examples of the liquid component include N-methyl-2-pyrrolidone and the like. Furthermore, when the composite material layer includes a first layer and a second layer, each layer can be formed by the above-mentioned method.
[0092] Each step in the formation of the composite material layer is not particularly limited, and known methods can be applied. For example, the coating of the slurry (or coating solution) can be carried out by a known method such as a method using a rod coater. In addition, drying can be carried out by a known method such as drying based on heating, natural drying, etc.
[0093] The spacer is formed on the composite material layer or the substrate layer. There is no particular limitation on the method for forming the spacer, and the spacer can be formed by the following method. First, a slurry or a coating liquid is prepared by mixing the components of the spacer and the liquid components. Then, the slurry or the coating liquid is applied to the portion where the spacer is to be formed and dried. In this way, the spacer can be formed. Examples of liquid components include N-methyl-2-pyrrolidone and the like. The slurry or the coating liquid can be applied using a dispenser or the like, or using a known printing method such as gravure printing, inkjet printing, and screen printing. In addition, drying can be carried out by a known method based on heating, natural drying, or the like. The diaphragm is obtained as described above.
[0094] The following is a specific description of examples of each component of the lithium secondary battery (L). Furthermore, the components described below are examples, and the components of the lithium secondary battery (L) of this embodiment are not limited to the following components. As components other than the characteristic parts of this embodiment, well-known components may also be used. As for the diaphragm and the spacer, they have been described above, so repeated descriptions are omitted.
[0095] [negative electrode]
[0096] The negative electrode includes a negative electrode collector. In a lithium secondary battery (L), lithium metal is deposited on the negative electrode collector by charging. More specifically, the lithium ions contained in the non-aqueous electrolyte accept electrons on the negative electrode collector by charging to become lithium metal, and are deposited on the negative electrode collector. The lithium metal deposited on the negative electrode collector is dissolved in the non-aqueous electrolyte in the form of lithium ions by discharging. Furthermore, the lithium ions contained in the non-aqueous electrolyte may be lithium ions derived from a lithium salt added to the non-aqueous electrolyte, may be lithium ions supplied from a positive electrode active material by charging, or may be both.
[0097] As the negative electrode current collector, a conductive sheet can be used. When the electrode group is a wound type, a strip-shaped conductive sheet can be used. Examples of the conductive sheet include conductive films, metal foils, and the like.
[0098] The surface of the conductive sheet can be smooth. As a result, during charging, lithium metal from the positive electrode is easily deposited evenly on the conductive sheet. Smooth means that the maximum height roughness Rz of the conductive sheet is less than 20 μm. The maximum height roughness Rz of the conductive sheet can also be less than 10 μm. The maximum height roughness Rz is measured in accordance with JIS (Japanese Industrial Standard) B 0601:2013.
[0099] The material of the negative electrode collector (conductive sheet) can be any conductive material other than lithium metal and lithium alloy. The conductive material can be a metal material such as a metal or an alloy. The conductive material is preferably a material that does not react with lithium. More specifically, it is preferably a material that does not form any alloy or intermetallic compound with lithium. Examples of such conductive materials include copper (Cu), nickel (Ni), iron (Fe), and alloys containing these metal elements, or graphite with the base surface preferentially exposed. As alloys, copper alloys, stainless steel (SUS), etc. can be listed. From the perspective of having high conductivity, copper and / or copper alloys are preferred. The thickness of the negative electrode collector is not particularly limited and can be in the range of 5 to 300 μm.
[0100] A negative electrode mixture layer may also be formed on the surface of the negative electrode current collector. The negative electrode mixture layer is formed, for example, by applying a paste containing a negative electrode active material such as graphite to at least a portion of the surface of the negative electrode current collector. However, from the perspective of realizing a lithium secondary battery with a high capacity exceeding that of a lithium ion battery, the thickness of the negative electrode mixture layer is set to be thin enough to allow lithium metal to precipitate on the negative electrode.
[0101] The negative electrode may include a negative electrode current collector and a sheet of lithium metal or lithium alloy disposed on the negative electrode current collector. That is, a base layer (a layer of lithium metal or lithium alloy) containing lithium metal may also be pre-set on the negative electrode current collector. Lithium alloys, in addition to lithium, may contain elements such as aluminum, magnesium, indium, and zinc. By pre-setting the base layer and allowing lithium metal to precipitate thereon during charging, dendritic precipitation can be more effectively suppressed. The thickness of the base layer is not particularly limited, and for example, may be in the range of 5 μm to 25 μm.
[0102] [positive electrode]
[0103] The positive electrode, for example, comprises a positive electrode current collector and a positive electrode mixture layer supported by the positive electrode current collector. The positive electrode mixture layer, for example, comprises a positive electrode active material, a conductive material, and a binder. The positive electrode mixture layer may be formed on only one side of the positive electrode current collector or on both sides thereof. The positive electrode is obtained, for example, by coating a positive electrode mixture slurry comprising a positive electrode active material, a conductive material, and a binder on both sides of the positive electrode current collector, and rolling the coating after drying the coating.
[0104] The positive electrode active material is a material that absorbs and releases lithium ions. As the positive electrode active material, for example, lithium-containing transition metal oxides, transition metal fluorides, polyanionic substances, fluorinated polyanionic substances, transition metal sulfides, etc. can be cited. Among them, lithium-containing transition metal oxides are preferred from the viewpoint of low manufacturing cost and high average discharge voltage.
[0105] As the transition metal element contained in the transition metal oxide containing lithium, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, W, etc. can be listed. The transition metal oxide containing lithium can contain one transition metal element, and can also contain two or more transition metal elements. The transition metal element can be Co, Ni and / or Mn. The transition metal oxide containing lithium can contain more than one typical element as needed. As typical elements, Mg, Al, Ca, Zn, Ga, Ge, Sn, Sb, Pb, Bi, etc. can be listed. The typical element can be Al, etc.
[0106] Among lithium-containing transition metal oxides, composite oxides containing Co, Ni and / or Mn as transition metal elements, sometimes containing Al as an arbitrary component, and having a layered rock salt type crystal structure are preferred in terms of obtaining high capacity. In this case, in a lithium secondary battery, the molar ratio of the total amount mLi of lithium in the positive electrode and the negative electrode to the amount mM of metal M other than lithium in the positive electrode, i.e., mLi / mM, can be set to, for example, 1.1 or less.
[0107] The conductive material is, for example, a carbon material, and examples of the carbon material include carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphite.
[0108] Examples of the binder include fluororesins, polyacrylonitrile, polyimide resins, acrylic resins, polyolefin resins, and rubber polymers. Examples of the fluororesins include polytetrafluoroethylene and polyvinylidene fluoride.
[0109] The positive electrode current collector may be any conductive sheet. A foil, a film, etc. may be used as the conductive sheet. A carbon material may be coated on the surface of the positive electrode current collector.
[0110] As the material of the positive electrode collector (conductive sheet), for example, metal materials including Al, Ti, Fe, etc. can be listed. The metal material can be Al, Al alloy, Ti, Ti alloy, Fe alloy, etc. The Fe alloy can be stainless steel (SUS). The thickness of the positive electrode collector is not particularly limited and can be in the range of 5 to 300 μm.
[0111] [Non-aqueous electrolyte]
[0112] The non-aqueous electrolyte having lithium ion conductivity includes, for example, a non-aqueous solvent, lithium ions and anions dissolved in the non-aqueous solvent. The non-aqueous electrolyte may be in a liquid state or a gel state.
[0113] The liquid non-aqueous electrolyte is prepared by dissolving a lithium salt in a non-aqueous solvent. When the lithium salt is dissolved in the non-aqueous solvent, lithium ions and anions are generated.
[0114] The gel-like non-aqueous electrolyte comprises a lithium salt and a matrix polymer, or comprises a lithium salt, a non-aqueous solvent and a matrix polymer. As the matrix polymer, for example, a polymer material that absorbs the non-aqueous solvent and gels can be used. As the polymer material, fluororesins, acrylic resins, polyether resins, etc. can be cited.
[0115] As the lithium salt or anion, a known lithium salt or anion used in a non-aqueous electrolyte of a lithium secondary battery can be used. Specifically, BF4 - 、ClO4 - PF6 - CF3SO3 - CF3CO2- , anions of imide compounds, anions of oxalate complexes, etc. Examples of anions of imide compounds include N(SO2CF3)2 - 、N(C m F 2m+1 SO2) x (C n F 2n+1 SO2) y - (m and n are each independently an integer greater than 0 or 1, x and y are each independently 0, 1 or 2, and x+y=2.) etc. The anion of the oxalate complex may contain boron and / or phosphorus. Examples of the anion of the oxalate complex include bisoxalate borate anion, BF2(C2O4) - PF4(C2O4) - 、PF2(C2O4)2 - The nonaqueous electrolyte may contain one of these anions alone, or may contain two or more of them.
[0116] From the viewpoint of suppressing the dendritic precipitation of lithium metal, it is preferred that the non-aqueous electrolyte contains at least anions of the oxalate complex. Through the interaction between the anions of the oxalate complex and lithium, the lithium metal is easily precipitated uniformly in the form of fine particles. Therefore, it is easy to suppress the local precipitation of lithium metal. It is also possible to combine the anions of the oxalate complex with other anions. The other anions can be PF6 - and / or imide-type anions.
[0117] The nonaqueous electrolyte may contain LiBF2(C2O4) (lithium difluorooxalatoborate) as a solute (lithium salt).
[0118] Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, or halogen-substituted products thereof. The non-aqueous electrolyte may contain one of these non-aqueous solvents alone, or may contain two or more of them. Examples of the halogen-substituted product include fluorides, etc.
[0119] As esters, for example, carbonates, carboxylates, etc. can be cited. As cyclic carbonates, ethylene carbonate, propylene carbonate, fluoroethylene carbonate (FEC), etc. can be cited. As chain carbonates, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate, etc. can be cited. As cyclic carboxylates, γ-butyrolactone, γ-valerolactone, etc. can be cited. As chain carboxylates, ethyl acetate, methyl propionate, methyl fluoropropionate, etc. can be cited.
[0120] Examples of ethers include cyclic ethers and chain ethers. Examples of cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, and 2-methyltetrahydrofuran. Examples of chain ethers include 1,2-dimethoxyethane, diethyl ether, ethyl vinyl ether, methyl phenyl ether, benzyl ethyl ether, diphenyl ether, dibenzyl ether, 1,2-diethoxyethane, and diethylene glycol dimethyl ether.
[0121] The concentration of the lithium salt in the non-aqueous electrolyte is, for example, 0.5 mol / L or more and 3.5 mol / L or less. The concentration of the anion in the non-aqueous electrolyte may be 0.5 mol / L or more and 3.5 mol / L or less. In addition, the concentration of the anion of the oxalate complex in the non-aqueous electrolyte may be 0.05 mol / L or more and 1 mol / L or less.
[0122] The non-aqueous electrolyte may also contain an additive. The additive may be a substance that forms a film on the negative electrode. By forming a film derived from the additive on the negative electrode, the formation of dendrites can be easily suppressed. Examples of such additives include vinylene carbonate, fluoroethylene carbonate (FEC), and vinyl ethyl carbonate (VEC).
[0123] [Exterior body]
[0124] The outer casing houses the positive electrode, the negative electrode, the separator, the spacer disposed on the separator, and the nonaqueous electrolyte. The outer casing is not particularly limited, and an outer casing used for a known lithium secondary battery can be used.
[0125] The present disclosure also discloses a composite component (C) for a battery. The composite component (C) includes the diaphragm and the spacer described as the constituent elements of the lithium secondary battery (L). That is, the composite component (C) includes the above-mentioned diaphragm and the spacer formed on the diaphragm. The diaphragm and the spacer have been described above, so repeated descriptions are omitted. The composite component (C) can be used as a diaphragm for a lithium secondary battery. The composite component (C) includes a diaphragm and a spacer, and the diaphragm has a substrate layer and a composite material layer. The spacer can be formed on the substrate layer or on the composite material layer.
[0126] If the width of the separator is too large, wrinkles are easily formed on the separator due to volume shrinkage during drying when the separator is formed. If wrinkles are formed on the separator, the formation of the wound electrode group is hindered and cracks are generated in the composite material layer. Since the separator of the composite member (C) has the above-mentioned specified size, the formation of wrinkles on the separator can be suppressed when the separator is formed.
[0127] An example of a lithium secondary battery (L) of the present embodiment is described in detail below with reference to the accompanying drawings. As the constituent elements of the lithium secondary battery of the example described below, the above-mentioned constituent elements can be applied. In addition, the constituent elements of the example described below can be changed based on the above-mentioned description. In addition, the matters described below can also be applied to the above-mentioned embodiment. In addition, in the lithium secondary battery described below, non-essential constituent elements in the lithium secondary battery of the present disclosure can also be omitted. Furthermore, in the following figures, the scales of the constituent elements are changed for easy understanding.
[0128] (Implementation Method 1)
[0129] Figure 1 FIG. 1 is a longitudinal cross-sectional view schematically showing an example of a lithium secondary battery according to Embodiment 1. Figure 1 In the figure, illustration of the spacer and the space formed by the spacer is omitted. Figure 1 The cylindrical lithium secondary battery 10 shown includes a cylindrical battery case, and a wound electrode group 14 and a non-aqueous electrolyte (not shown) housed in the battery case. The battery case includes: a case body 15 as a bottomed cylindrical metal container, and a sealing body 16 that seals the opening of the case body 15. A gasket 27 is arranged between the case body 15 and the sealing body 16. The airtightness of the battery case is ensured by the gasket 27. In the case body 15, insulating plates 17 and 18 are respectively arranged at both ends of the electrode group 14 in the winding axis direction.
[0130] The housing body 15 has a step portion 21 formed by partially pressing the side wall of the housing body 15 from the outside, for example. The step portion 21 may be formed in an annular shape on the side wall of the housing body 15 along the circumferential direction of the housing body 15. In this case, the sealing body 16 is supported by the surface of the step portion 21 on the opening side.
[0131] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25 and a cap 26. In the sealing body 16, these components are stacked in this order. The sealing body 16 is installed on the opening of the shell body 15 in such a way that the cap 26 is located on the outer side of the shell body 15 and the filter 22 is located on the inner side of the shell body 15. The above-mentioned components constituting the sealing body 16 are, for example, in the shape of a circular plate or a ring. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, and an insulating member 24 is interposed between their respective peripheral portions. The filter 22 and the lower valve body 23 are connected to each other at their respective central portions. The upper valve body 25 and the cap 26 are connected to each other at their respective central portions. That is, the components except the insulating member 24 are electrically connected to each other.
[0132] A vent hole (not shown) is formed in the lower valve body 23. Therefore, if the internal pressure of the battery case rises due to abnormal heating or the like, the upper valve body 25 bulges toward the cover 26 and separates from the lower valve body 23. As a result, the electrical connection between the lower valve body 23 and the upper valve body 25 is cut off. If the internal pressure rises further, the upper valve body 25 breaks, and gas is discharged from an opening (not shown) formed in the cover 26.
[0133] Figure 2 It is an enlarged view of a part of the electrode group 14 . Figure 2 Include Figure 1 The part near the positive electrode surrounded by region II and Figure 1 The portion near the negative electrode surrounded by region III.
[0134] The electrode group 14 includes a positive electrode 11, a negative electrode 12, a separator 50, and a separator 53. The positive electrode 11, the negative electrode 12, and the separator 50 are all in a strip shape. The separator 53 is formed on the separator 50 (composite material layer 52). The positive electrode 11, the negative electrode 12, and the separator 50 are wound in such a manner that the separator 50 is arranged between the positive electrode and the negative electrode 12, thereby forming the electrode group 14.
[0135] The positive electrode 11 includes a positive electrode current collector 11a and a positive electrode mixture layer 11b. The positive electrode current collector 11a is electrically connected to a cap 26 that functions as a positive electrode terminal via a positive electrode lead 19. Figure 2 In FIG. 1 , a negative electrode (negative electrode current collector) in a state where lithium metal is not deposited is shown as the negative electrode 12 . The negative electrode 12 is electrically connected to the case body 15 functioning as a negative electrode terminal via a negative electrode lead 20 .
[0136] like Figure 2 As shown, the separator 50 includes a substrate layer 51 and a composite material layer 52. The separator 50 has a first main surface 50a facing the negative electrode 12 and a second main surface 50b facing the positive electrode 11. Figure 2 In the example shown, the spacer 53 is formed on the first main surface 50 a. The composite member (C) described above includes the diaphragm 50 and the spacer 53 .
[0137] In the first embodiment, the composite material layer 52 is formed on the main surface on the negative electrode 12 side of the two main surfaces of the substrate layer 51. The separator 53 is formed on the composite material layer 52 and is in contact with the negative electrode 12. The separator 53 forms a space 14s between the positive electrode 11 and the negative electrode 12 (between the negative electrode 12 and the separator 50). Figure 2 The height h of the spacer 53 is shown.
[0138] In the lithium secondary battery 10, during charging, lithium metal is deposited on the negative electrode 12. Since there is a space 14s between the positive electrode 11 and the negative electrode 12, the volume change of the electrode group 14 accompanying the deposition of lithium metal is reduced, and the cycle characteristics are improved.
[0139] Figure 3 An example of the planar shape of the spacer 53 is shown. Figure 4 Show Figure 3 A partial enlarged view of the Figure 3 In one example, the spacer 53 is composed of linear protrusions 53a. The linear protrusions 53a are arranged in a mesh shape, and more specifically, are uniformly formed in a honeycomb pattern. The honeycomb pattern is a pattern in which a plurality of hexagons are arranged in a manner that shares edges with each other. The area where the linear protrusions 53a are not formed constitutes the space 14s. Figure 4 1 shows the width W of the linear projection 53a. The width W of the linear projection is the length (width) of the linear projection 53a in a direction perpendicular to the direction in which the linear projection 53a extends in a plan view.
[0140] Figure 5 to Figure 7 Another example of the planar shape of the spacer 53 is shown. Figure 3 to Figure 7 This is a diagram showing a plan view of the diaphragm 50 and the spacer 53 . Figure 5 The spacer 53 includes a plurality of linear protrusions 53a separated from each other. There is a gap P between the linear protrusions 53a. The area where the linear protrusions 53a are not formed constitutes the space 14s. Figure 6 The spacer 53 includes a plurality of linear protrusions 53 a arranged in a stripe shape. Figure 7 The spacer 53 includes a plurality of linear protrusions 53 a arranged in a lattice pattern.
[0141] In Embodiment 1, a cylindrical lithium secondary battery having a wound electrode group is described. However, the lithium secondary battery of this embodiment is not limited to the method of Embodiment 1, and can also be applied to other methods. The shape of the lithium secondary battery can be appropriately selected from various shapes such as cylindrical, coin-shaped, square, sheet-shaped, flat, etc. according to its use. The form of the electrode group is not particularly limited, and it can also be a stacked type.
[0142] (Note)
[0143] The following techniques are disclosed through the description of the above embodiments.
[0144] (Technology 1)
[0145] A lithium secondary battery,
[0146] The invention comprises a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, a separator arranged on the separator, and a non-aqueous electrolyte having lithium ion conductivity.
[0147] The negative electrode is an electrode from which lithium metal is deposited during charging and dissolved during discharging.
[0148] The diaphragm comprises a substrate layer and a composite material layer,
[0149] In a plan view, the shortest distance from any point on the spacer to the outer edge of the spacer is less than 1.5 mm, and the width of the spacer is greater than 0.01 mm.
[0150] The composite material layer contains a polymer and inorganic particles.
[0151] (Technique 2)
[0152] In the lithium secondary battery according to technology 1, the composite material layer is a porous layer.
[0153] (Technique 3)
[0154] In the lithium secondary battery according to technology 1 or 2, the polymer includes at least one selected from aromatic polyamide, aromatic polyimide, and aromatic polyamideimide.
[0155] (Technique 4)
[0156] The lithium secondary battery according to any one of techniques 1 to 3,
[0157] The separator has a first main surface facing the negative electrode and a second main surface facing the positive electrode.
[0158] The spacer is formed on the first main surface.
[0159] (Technique 5)
[0160] In the lithium secondary battery according to any one of techniques 1 to 4, the separator is formed on the composite material layer.
[0161] (Technique 6)
[0162] In the lithium secondary battery according to any one of techniques 1 to 5, the separator includes linear protrusions.
[0163] (Technique 7)
[0164] According to the lithium secondary battery of the sixth aspect, the planar shape of the linear projection is a shape formed by combining polygons.
[0165] (Technology 8)
[0166] According to the lithium secondary battery of technology 6, the planar shape of the linear protrusions is a honeycomb shape.
[0167] (Technique 9)
[0168] According to the lithium secondary battery of technology 6, the linear protrusions include a plurality of linear protrusions arranged in a stripe shape.
[0169] (Technology 10)
[0170] A composite component,
[0171] The invention comprises a diaphragm and a spacer, wherein the diaphragm has a substrate layer and a composite material layer,
[0172] In a plan view, the shortest distance from any point on the spacer to the outer edge of the spacer is less than 1.5 mm, and the width of the spacer is greater than 0.01 mm.
[0173] The composite material layer contains a polymer and inorganic particles.
[0174] (Technology 11)
[0175] According to the composite member of Technology 10, the composite material layer is a porous layer.
[0176] (Technology 12)
[0177] In the composite member according to the technique 10 or 11, the polymer includes at least one selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide.
[0178] (Technology 13)
[0179] According to the composite member of any one of Techniques 10 to 12, the spacer is formed on the composite material layer.
[0180] (Technology 14)
[0181] In the composite member according to any one of Techniques 10 to 13, the spacer includes a linear protrusion.
[0182] (Technology 15)
[0183] According to the composite member described in the fourteenth technique, the planar shape of the linear projection is a shape formed by combining polygons.
[0184] (Technology 16)
[0185] According to the composite member described in Technology 14, the planar shape of the linear protrusions is a honeycomb shape.
[0186] (Technology 17)
[0187] According to the composite member described in Technology 14, the linear protrusions include a plurality of linear protrusions arranged in a stripe shape.
[0188] [Example]
[0189] The lithium secondary battery (L) of this embodiment will be described in detail below based on examples. The present disclosure is not limited to the following examples.
[0190] (Battery A1)
[0191] The lithium secondary battery A1 was produced by the following steps.
[0192] (1) Preparation of positive electrode
[0193] A rock salt-type lithium-containing transition metal oxide (NCA: positive electrode active material) containing Li, Ni, Co and Al (the molar ratio of Li to the total of Ni, Co and Al is 1.0) and having a layered structure is prepared. The lithium-containing transition metal oxide (NCA), acetylene black (AB; conductive material) and polyvinylidene fluoride (PVdF; binder) are mixed in a mass ratio of NCA:AB:PVdF=95:2.5:2.5, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added and stirred to prepare a positive electrode mixture slurry. Then, the obtained positive electrode mixture slurry is applied to both sides of a strip of Al foil (positive electrode collector) and dried, thereby forming a coating film of the positive electrode mixture. Then, the coating film is rolled using a roller. Finally, the obtained positive electrode collector and the positive electrode mixture stack are cut into a specified electrode size to produce a positive electrode having a positive electrode mixture layer on both sides of the positive electrode collector.
[0194] (2) Preparation of negative electrode
[0195] As the negative electrode, a negative electrode having rolled lithium metal layers (25 μm thick) provided on both surfaces of a strip-shaped copper foil (12 μm thick) was used.
[0196] (3) Fabrication of diaphragms and spacers
[0197] First, a polyethylene strip-shaped porous film (average thickness 10 μm) was prepared as a substrate layer. Then, a porous composite material layer (average thickness 2 μm) was formed on one side of the substrate layer. The composite material layer was formed by sequentially forming a second layer and a first layer on the substrate layer.
[0198] The second layer is formed as follows. First, N-methyl-2-pyrrolidone (NMP) and calcium chloride are mixed in a mass ratio of 94.2:5.8. The mixture is heated to about 80°C to completely dissolve the calcium chloride. Then, the solution is returned to room temperature, and after taking 2200 g, 0.6 mol of p-phenylenediamine (PPD) is added to completely dissolve it. While maintaining the solution at about 20°C, 0.6 mol of terephthaloyl chloride (TPC) is added in small amounts each time. The obtained solution is aged at about 20°C for 1 hour to prepare a polymerization solution. Next, 100 g of the polymerization solution is mixed with an N-methyl-2-pyrrolidone solution in which 5.8% by mass of calcium chloride is dissolved to obtain a solution (coating solution) having a concentration of 2% by mass of poly(p-phenylene terephthalamide) (PPTA) as an aromatic polyamide (aromatic polyamide).
[0199] Next, the coating solution was applied to the substrate layer by slit die extrusion coating to form a coating film. Next, the substrate layer with the coating film was placed in an atmosphere of 25°C and 70% relative humidity for 1 hour to precipitate the aromatic polyamide. Next, the NMP and calcium chloride in the coating film were removed by water washing. Next, the coating film was dried at 60°C for 5 minutes to form the second layer.
[0200] The first layer is formed as follows. First, lithium phosphate (Li3PO4) particles and poly (N-vinyl acetamide) (PNVA) are mixed in a mass ratio of 100:8 to obtain a mixture. As lithium phosphate particles, lithium phosphate particles having a volume-based median diameter of 0.19 μm are used. Water (ion exchange water) is added to the obtained mixture and stirred to prepare a slurry (coating liquid) having a solid content concentration of 12% by mass. Next, the slurry is applied to the second layer by microgravure coating to form a coating film. Next, the coating film is dried using a drying oven attached to the coating machine. In this way, the first layer is formed. In this way, a composite material layer is formed.
[0201] Next, a coating solution containing polyvinylidene fluoride and aluminum oxide particles (inorganic filler) was dispensed using a dispenser to form Figure 6 The coating liquid is then vacuum dried. Figure 6 The stripe-shaped non-porous separator shown in FIG. 1 was formed so that each linear protrusion had an average height of 30 μm and a width W of 0.01 mm.
[0202] (4) Preparation of non-aqueous electrolyte
[0203] Ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed at a volume ratio of EC:DMC=30:70. LiPF6 and LiBF2 (C2O4) were dissolved in the obtained mixed solvent in such a manner that the concentration was 1 mol / L and 0.1 mol / L, respectively, to prepare a liquid non-aqueous electrolyte.
[0204] (5) Battery production
[0205] The positive electrode obtained above was provided with an Al tab. The negative electrode was provided with a Ni tab. In an inert gas atmosphere, the positive electrode and the negative electrode were wound in a spiral shape with a separator therebetween to produce a wound electrode group. At this time, the separator was arranged so that the separator was opposite to the positive electrode.
[0206] The obtained electrode group was housed in a bag-shaped outer casing formed of a laminate sheet having an Al layer, and the nonaqueous electrolyte was injected into the outer casing housing the electrode group, and then the outer casing was sealed. In this manner, a lithium secondary battery A1 was produced.
[0207] (Battery A2)
[0208] Battery A2 was produced by the same method and conditions as Battery A1 except that the pattern of the spacers was changed. Figure 3 The honeycomb pattern shown forms the separator. The height and width of the linear protrusions are the same as those of the separator of battery A1.
[0209] (Batteries A3 to A5 and Batteries C2 to C9)
[0210] Batteries A3 to A5 and Batteries C2 to C9 were produced by the same method and conditions as Battery A1, except that the pattern of the spacer, the width W of the linear protrusion, the presence or absence of the composite material layer, and the electrode opposite to the spacer (the direction of the separator arrangement) were changed as shown in Table 1. In addition, in all batteries, the average height of the spacer was the same as the average height of the spacer of Battery A1 (30 μm). In Battery C7, a non-porous layer formed only of a polymer was arranged in place of the composite material layer.
[0211] (Battery C1)
[0212] Battery C1 was produced by the same method and conditions as Battery A1 except that the composite material layer and the separator were not formed. The separator of Battery C1 consisted of only the substrate layer, and no separator was formed on the substrate layer.
[0213] The plurality of batteries produced as described above were evaluated by the following method.
[0214] (Charge and discharge test)
[0215] The obtained batteries were subjected to a charge and discharge test. In the charge and discharge test, the batteries were charged in a thermostatic chamber at 25° C. under the following conditions, rested for 20 minutes, and then discharged under the following conditions.
[0216] (Charge)
[0217] The battery was charged at a constant current of 2.15 mA per unit area (cm2) of the electrode until the battery voltage reached 4.1 V, and then charged at a constant voltage of 4.1 V until the current value per unit area of the electrode reached 0.54 mA.
[0218] (Discharge)
[0219] Constant current discharge was performed at a current of 2.15 mA per unit area of the electrode until the battery voltage reached 3.75V.
[0220] (Discharge capacity maintenance rate)
[0221] In the above-mentioned charge and discharge test, the discharge capacity C(1) at the first cycle and the discharge capacity C(50) at the 50th cycle were measured. Then, the discharge capacity retention rate was calculated by the following formula.
[0222] Discharge capacity retention rate (%) = 100 × C (50) / C (1)
[0223] (Expansion rate near the negative electrode)
[0224] The above-mentioned charge and discharge are regarded as one cycle, and the manufactured battery is charged to the second cycle. Then, the battery before charge and discharge and the battery charged to the second cycle are disassembled respectively, and the stack of the positive electrode, the negative electrode and the two separators on both sides of the negative electrode is taken out. Disassembly is carried out in an inert gas atmosphere. The stack of the positive electrode, the negative electrode and the separator taken out is washed with dimethyl carbonate and dried, and the thickness of the stack is measured. The thickness of the stack is measured using a Peacock Digital Thickness Gauge G2-205M. Then, the thickness is measured at any 5 points in the stack, and the arithmetic mean of the 5 measured values is taken as the average thickness of the stack. Next, the average thickness X obtained by subtracting the thickness of the two substrate layers and the thickness of the two composite material layers from the average thickness is calculated. Then, using the average thickness X(0) before charge and discharge and the average thickness X(2) of the second cycle, the expansion rate (%) near the negative electrode is calculated using the following formula.
[0225] Expansion rate near the negative electrode (%) = 100 × (X (2) - X (0)) / X (0)
[0226] Table 1 shows some of the battery production conditions and evaluation results.
[0227] Table 1
[0228]
[0229] Batteries A1 to A5 are batteries of the present disclosure, and batteries C1 to C9 are batteries of comparative examples. Furthermore, the shortest distance D of the spacers of batteries C8 and C9 is 1.5 mm. Batteries A1 to A5 can suppress expansion near the negative electrode and achieve a high capacity retention rate (good cycle characteristics).
[0230] Industrial Applicability
[0231] The present disclosure can be applied to lithium secondary batteries and composite components. For example, the lithium secondary batteries of the present disclosure can be used in electronic devices such as portable phones, smart phones and tablet terminals, electric vehicles including hybrid vehicles and plug-in hybrid vehicles, household storage batteries combined with solar cells, etc.
[0232] The present invention has been described by present preferred embodiments, but such disclosure should not be interpreted in a limiting sense. For those skilled in the art of the present invention, various modifications and changes will undoubtedly come to mind by reading the above disclosure. Therefore, the claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present invention.
[0233] Description of Reference Numerals
[0234] 10: Lithium secondary battery
[0235] 11: Positive electrode
[0236] 12: Negative electrode
[0237] 14: Electrode Group
[0238] 14s: Space
[0239] 50: Diaphragm
[0240] 51: Base material layer
[0241] 50a, 50b: Main surface
[0242] 52: Composite material layer
[0243] 53: Spacer
[0244] 53a: convex part
Claims
1. A lithium secondary battery, The invention comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, a separator disposed on the separator, and a non-aqueous electrolyte having lithium ion conductivity. The negative electrode is an electrode from which lithium metal is deposited during charging and dissolved during discharging. The diaphragm comprises a substrate layer and a composite material layer, In a plan view, the shortest distance from any point on the spacer to the outer edge of the spacer is less than 1.5 mm, and the width of the spacer is greater than 0.01 mm. The composite material layer contains a polymer and inorganic particles.
2. The lithium secondary battery according to claim 1, The composite material layer is a porous layer.
3. The lithium secondary battery according to claim 1 or 2, The polymer includes at least one selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide.
4. The lithium secondary battery according to claim 1 or 2, The separator has a first main surface facing the negative electrode and a second main surface facing the positive electrode. The spacer is formed on the first main surface.
5. The lithium secondary battery according to claim 1 or 2, The spacer is formed on the composite material layer.
6. The lithium secondary battery according to claim 1 or 2, The spacer includes a linear protrusion. 7 . The lithium secondary battery according to claim 6 , wherein the planar shape of the linear projection is a shape formed by combining polygons.
8. The lithium secondary battery according to claim 6, The planar shape of the linear protrusions is a honeycomb shape.
9. The lithium secondary battery according to claim 6, The linear protrusions include a plurality of linear protrusions arranged in a stripe shape.
10. A composite component, The invention comprises a diaphragm and a spacer, wherein the diaphragm has a substrate layer and a composite material layer, In a plan view, the shortest distance from any point on the spacer to the outer edge of the spacer is less than 1.5 mm, and the width of the spacer is greater than 0.01 mm. The composite material layer contains a polymer and inorganic particles.
11. The composite component according to claim 10, The composite material layer is a porous layer.
12. The composite component according to claim 10 or 11, The polymer includes at least one selected from the group consisting of aromatic polyamide, aromatic polyimide, and aromatic polyamideimide.
13. The composite component according to claim 10 or 11, The spacer is formed on the composite material layer.
14. The composite component according to claim 10 or 11, The spacer includes a linear protrusion.
15. The composite component according to claim 14, The planar shape of the linear protrusion is a shape formed by combining polygons.
16. The composite member according to claim 14, The planar shape of the linear protrusions is a honeycomb shape.
17. The composite member according to claim 14, The linear protrusions include a plurality of linear protrusions arranged in a stripe shape.
Citation Information
Patent Citations
Lithium secondary battery
WO2020066254A1